Role of Procalcitonin and C-reactive Protein as Marker of Sepsis in Major Burn Patients: A Systematic Review and Meta-analysis - Permatasari, A. A. I. Yulan; Sanjaya, I. G. P. Hendra; Widiana, I. Gde Raka; Niryana, I. Wayan; Asmarajaya, A. A. G. Ngurah; Hamid, Agus Roy R. H.; Adnyana, M. Suka (Open Access Macedonian Journal of Medical Sciences, 2021)
AIM: Although absolute values for C-reactive protein (CRP) and procalcitonin (PCT) are well known to predict sepsis, it remains unclear how their diagnostic value in major burn patients as metabolic changes in burn patient mimic signs and symptoms for sepsis. This paper attempts to clarify these points for both of the markers. METHODS: A comprehensive literature search of PubMed, Scopus, DOAJ, Web of Science, and the Cochrane Library databases for studies published up to June 1, 2020, that evaluated PCT and/or CRP as a marker for diagnosing sepsis in burn patients was conducted. Review Manager 5.3 was used to analyze the data. RESULTS: A total of 11 literatures were obtained. The combined sensitivity and specificity for PCT as assessed by meta-analysis were 88% and 89%, respectively. The combined sensitivity and specificity of CRP were described as 85.5% and 57.5%, respectively. Meta-analysis cannot be performed for CRP parameters because there are only two literatures that include CRP diagnostic test values. DISCUSSION: PCT and CRP have additional diagnostic value for sepsis in patients with major burns. The pooled sensitivity and specificity of PCT are excellent. Although the difference in sensitivity between PCT and CRP is not very large, there are distinct differences in specificity. A low CRP specificity value will show many “false positives” when CRP is used as a biomarker. CONCLUSION: PCT provides a better diagnostic value than CRP in cases of sepsis in major burn patients. More study on combination of biomarker, clinical presentation, and microbial culture for diagnosing sepsis are needed. Further large-scale research with cohort or case control design should be done.